Influência do fator de crescimento semelhante à insulina I (IGF-I) adicionado ao meio fluido sintético de tuba uterina (SOF) sobre a maturação in vitro de oócitos caninos (Canis familiaris) - Machado, Marco Antonio [UNESP]; Toniollo, Gilson Hélio [UNESP]; Oliveira, Kellen [UNESP] (Universidade Estadual de Londrina (UEL), 2007)
The follicular growth and oocyte maturation knowledge are very important to the development and improvement of new biotechnologies such as in vitro fertilization and somatic cell nuclear transfer. In order to the necessity of clarify the basic mechanisms related to canine oocyte maturation, this investigation focuses on the evaluation of the effect of insulin-like growth factor-i (IGF-I), added to synthetic oviductal fluid medium (SOF) on the in vitro maturation of domestic dog oocytes. Thirty-seven bitches undergoing ovariohysterectomy for castration or due to pathological conditions of the uterus were selected as oocytes' donors (n=875). The oocytes were allocated in the following groups: MO (stained in the collection's time), Control (72h in SOF) and Experimental (72h in SOF plus 100 ng IGF-I). After 72 hours of maturation the oocytes' nuclear status were assessed by Hoechst 33342 dye. The best results in terms of oocyte harvest were observed in those juvenile donors,, females in estrus, nuliparous and pure breeds. No significant differences were observed between treatments control (SOF) or experimental (IGF-I).
The effect of the synthetic oviductal fluid medium (SOF) supplemented with insulin-like growth factor-I (IGF-I) on in vitro maturation of canine oocytes (Canis familiaris)
Keywords: IVM; nuclear maturation; Oocyte; bitch; IGF-I; SOF